Essays on Unemployment Insurance - Gerhard Castro de Britto, Diogo <1987> (Alma Mater Studiorum - Università di Bologna, 2015)
Can the potential availability of unemployment insurance (UI) affect the behavior of employed workers and the duration of their employment spells? After discussing few straightforward reasons why UI may affect employment duration, I apply a regression kink design (RKD) to address this question using linked employer-employee data from the Brazilian labor market. Exploiting the UI schedule, I find that potential benefit level significantly affects the duration of employment spells. This effect is local to low skilled workers and, surprisingly, indicates that a 1% increase in unemployment benefits increases job duration by around 0.3%. Such result is driven by the fact that higher UI decreases the probability of job quits, which are not covered by UI in Brazil. These estimates are robust to permutation tests and a number of falsification tests. I develop a reduced-form welfare formula to assess the economic relevance of this result. Based on that, I show that the positive effect on employment duration implies in a higher optimal benefit level. Moreover, the formula shows that the elasticity of employment duration impacts welfare just with the same weight as the well-known elasticity of unemployment duration to benefit level.